ASSESSING SUSTAINABILITY OF THE SOUTHEAST EUROPEAN ECONOMIES - Petrov, Viktorija; Trivić, Nada; Ćelić, Đorđe (Economics of Agriculture, 2018)
Sustainable development is development that meets the needs of the present, without compromising the ability of future generations to meet their own needs. Sustainability indicators are based on the attempt to measure or determine the path of development of the economy in two directions: sustaining human wellbeing, or preserving the capacity to provide wellbeing. The research has been conducted to assess sustainability in the Southeast Europe, represented with a group of 10 countries with the 15 multi-metric indicators. A cluster analysis was performed on the set of indices to check the formation of distinctive clusters. Albania, Bosnia and Herzegovina, Macedonia, Montenegro and Serbia constitute frst cluster, proving small differences among data. Second cluster consists of Bulgaria, Croatia and Romania, while last cluster consists of only Greece and Slovenia.